Morphology and properties of silica-based coatings with different functionalities for Fe3O4, ZnO and Al2O3 nanoparticles1. Issue 59 (28th June 2015) - Liu, D.; Pourrahimi, A. M.; Pallon, L. K. H.; Andersson, R. L.; Hedenqvist, M. S.; Gedde, U. W.; Olsson, R. T.
<x xml:space="preserve">Abstract</x> A facile single-step method for obtaining 2–3 nm thick silsesquioxane coatings on metal oxide nanoparticles using different carbon-functional silane precursors is presented.